Consumer behavior - Rettie, Ruth (Henry Stewart Talks, 2010)
Internet consumer behavior, Review of usage data, Use by age, income and education, Internet consumer dynamics, Economies of scale and scope, Internet empowers consumers, Changing the consumer/brand relationship, Importance of user generated content, Virtual product placement, Social psychology perspective, Captology: computers as persuasive technologies, Cialdini's six principles of social influence
Archived at 2022/04/12